2022
DOI: 10.1126/sciadv.abo0375
|View full text |Cite
|
Sign up to set email alerts
|

Twisted black phosphorus–based van der Waals stacks for fiber-integrated polarimeters

Abstract: The real-time, in-line analysis of light polarization is critical in optical networks, currently suffering from complex systems with numerous bulky opto-electro-mechanical elements tandemly arranged along the optical path. Here, we design and fabricate a fiber-integrated polarimeter by vertically stacking three photodetection units based on six-layer van der Waals materials, including one bismuth selenide (Bi 2 Se 3 ) layer for power calibration, two twisted blac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Figure S4 (Supporting Information) shows the 2D plot of the measured polarization‐resolved photocurrent for those two stacked ReS 2 nanobelt devices illuminated by a linearly polarized light with defined polarization directions under different excitation wavelengths and excitation powers. The color dots are experimental data, which can be fitted by the closed elliptic equation, (a I 1 + bI 2 + c ) 2 + ( dI 1 + e ) 2 = 1 [ 34 ] where a , b , c , d , and e are fitting parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Figure S4 (Supporting Information) shows the 2D plot of the measured polarization‐resolved photocurrent for those two stacked ReS 2 nanobelt devices illuminated by a linearly polarized light with defined polarization directions under different excitation wavelengths and excitation powers. The color dots are experimental data, which can be fitted by the closed elliptic equation, (a I 1 + bI 2 + c ) 2 + ( dI 1 + e ) 2 = 1 [ 34 ] where a , b , c , d , and e are fitting parameters.…”
Section: Resultsmentioning
confidence: 99%
“…10e). 180 They established the following relationship between photocurrent ( I ), light power ( P ) and polarization angle ( φ ): I = m · P n , I = I C ·sin(2 φ ) + I L ·sin(4 φ + φ 0 ) + I 0 , where m and n are fitting coefficients, and φ , φ 0 and I 0 are the polarized angle, initial polarized angle and light power, respectively. The in-plane anisotropic properties of BP and ingenious geometric structure of devices are mainly considered.…”
Section: Properties and Applicationsmentioning
confidence: 99%
“…Based on these advantages, recent research has demonstrated the potential of quasi-1D materials in high-performance polarization-selective optoelectronic and nanophotonic devices, such as polarization-selective optical sensors and polarized-light emitters. [12][13][14][15][16][17][18][19][20][21] In particular, the combination of their optical anisotropy with low-dimensionalityoriginated ultrafast photoresponse enables polarization-driven optical modulations on femtosecond and picosecond time scales. [22][23][24][25][26][27] This makes quasi-1D materials an ideal platform for realizing polarization-selective and polarization-controlled ultrafast optical switches and modulators, essential components for high-speed optical information processing.…”
Section: Introductionmentioning
confidence: 99%